Analyzing Public Perception on Integrating Ride-Hailing with Emergency Health Services - Tubagus Robbi Megantara; Rizki Apriva Hidayana; Indah Mauludina Hasanah (Rescollacom (Research Collaborations Community), 2026)
Traditional Emergency Health Services (EHS) face numerous challenges, including response time efficiency. The integration of ride-hailing platforms offers an innovative solution, yet public perception of this concept remains underexplored. This study investigates public perception through a quantitative survey of 100 respondents, analyzed as a whole and as two subgroups: those with prior EHS experience (n=48) and those without (n=52). The results reveal exceptionally strong and broad public support for this integration. A key finding is a significant